Design of a Collaborative Learning Platform Based on Problem-Based Learning for Distance Education: A Preliminary Study - Suciana, Dola; Wathi, Ayu Fahimah Diniyah; Mabukin, Faizal Akhmad Adi; Sausan, Inas; Wijayanti, Sukma Wahyu (Universitas Pendidikan Mandalika, 2025)
This study aims to design and validate an initial concept of a collaborative Problem-Based Learning (PBL)-based learning platform tailored for the context of distance learning. The research employed a descriptive-exploratory design with a mixed-methods approach. Quantitative data were collected through a 5-point Likert scale questionnaire administered to 23 chemistry education students, while qualitative data were obtained from open-ended questions and expert reviews involving four subject matter experts. Quantitative data were analyzed using descriptive statistical techniques, including the calculation of mean scores and reliability testing with Cronbach’s Alpha, whereas qualitative data were analyzed through thematic analysis to identify key themes and insights. The results indicate high user demand for integrated features, including scheduled consultations with lecturers (M = 4.52), collaborative group work within a single platform (M = 4.39), direct upload and feedback mechanisms (M = 4.26), activity logs and contribution rubrics (M = 4.21), and online project presentations (M = 4.17). Expert evaluations confirmed the alignment of the proposed design with PBL stages while emphasizing three prerequisites for implementation: (i) an intuitive interface that minimizes user cognitive load, (ii) concise orientation or training sessions for both lecturers and students, and (iii) connectivity mitigation strategies such as low-bandwidth modes and asynchronous alternatives. These findings provide an evidence-based foundation for subsequent prototyping and pilot testing to ensure the platform’s effectiveness in enhancing collaboration, process transparency, and learner engagement in distance PBL contexts. The study's outcomes are expected to contribute to the development of innovative learning platforms that support student-centered learning and foster collaborative problem-solving skills in online learning environments.